1999
DOI: 10.3406/intel.1999.1778
|View full text |Cite
|
Sign up to set email alerts
|

Sens et temps de la Gestalt

Abstract: La Gestalttheorie n’est pas seulement un corps de doctrine commun à plusieurs écoles de l’histoire de la psychologie : elle s’est voulue d’abord une théorie universelle des formes et des organisations, ayant vocation à valoir dans une pluralité de champs scientifiques dont elle aurait constitué un principe d’unification. Cet article dresse un inventaire de son héritage, et cherche à déterminer le rôle qu'elle pourrait jouer à nouveau dans les sciences cognitives. A cette fin, nous évoquerons d’abord le context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
14

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
0
8
0
14
Order By: Relevance
“…Wertheimer (1923) suggested that we comprehend the whole before distinguishing the parts, if the latter occurs at all. In the same vein, Rosenthal and Visetti (1999) emphasized that the perceptual field is not composed of separate elements or of elements that are first given; on the contrary, the field produces and distributes the elements in time (p. 161). In summary, it seems reasonable to assume that a visual pattern is perceived and memorized as a whole, with the elements taking their place accordingly.…”
Section: Dynamics Of the Configuration And Dynamics Of The Elementsmentioning
confidence: 96%
“…Wertheimer (1923) suggested that we comprehend the whole before distinguishing the parts, if the latter occurs at all. In the same vein, Rosenthal and Visetti (1999) emphasized that the perceptual field is not composed of separate elements or of elements that are first given; on the contrary, the field produces and distributes the elements in time (p. 161). In summary, it seems reasonable to assume that a visual pattern is perceived and memorized as a whole, with the elements taking their place accordingly.…”
Section: Dynamics Of the Configuration And Dynamics Of The Elementsmentioning
confidence: 96%
“…As for the term perception, it must be understood both in a gestaltist and in a constructivist conception. From the gestalt theory, (Köhler 1929;Guillaume 1979;Rosenthal and Visetti 1999), we use the principle of organizational activity of the subject, according to the Law of Proximity, the Law of Similarity, the Law of Continuity, the Law of Closure, and the Law of Good Form-to name the most relevant ones. Fundamentally, the meaning of a sentence is not the addition of ''bits of meaning'' but rather corresponds to what gestalt psychologists call a ''good form'' that is to say, the piecing together of elements manifesting the principles mentioned before and corresponding to the simplest, most balanced, and most stable form.…”
Section: Perception Of Meaning and Comprehension Of Meaningmentioning
confidence: 99%
“…Le cadre de la Gestalttheorie a été retenu dans ses ancrages phénoménologiques pour considérer la conduite motrice comme une totalité dynamique et signifiante pour celui qui la réalise (Guillaume, 1937 ;Rosenthal et Visetti, 1999, 2003. De ce point de vue, tous les actes humains ont un sens, même ceux qui paraissent a priori anodins.…”
Section: Quels Savoir Pour Guider Les Apprentissages Des éLèves ?unclassified